Subject Description of Fiction - Macaj, Edlira (Richtmann Publishing, 2012)
According to organisation of information, libraries try to be helpful to its users. When question comes at the fictionclassification, there might be needed much more attention, as the fiction material suggest multiple interpretations.Purpose: describinghow the fiction classification is in public libraries of Albania and what lacks; seeking through possibilities how to enhance the subjectdescription by applicating new ways, adoptable in future steps. Approach: Revealing fiction preferences percentages among users inpublic libraries need concrete data. Three main public libraries were object of study. Fiction is opened to variables interpretations.There should be accurate identifications for shelves purposes and enhanced subject descriptions. An analitic discourse help on issue.Descriptions and explanations need a qualitative method. Value: by using new tools (labels, signs, words, etc.) for subject descriptionfor quick choices and library future catalogs the result is the increasement of users satisfaction, which is a library mission too.Limits:New proposals for fiction description might be useful, helpful, but it also takes the risk of too much â€œwateryâ€ information. Some of themmay confuse the unspecialised user, attracted by fiction section. Some of users donâ€™t need to much details. Conclusion: New formsfound for subject description of fiction are indispensable and make easy the searching process. Users arenâ€™t interested if tools arewords, numbers, lables or signs. Whatever they are, they should be the right one to be useful on technical developments.